ANALISIS STRATEGI QRIS OLEH KPWBI DKI JAKARTA DALAM UPAYA PENGEMBANGAN PEMBAYARAN NONTUNAI PADA UMKM JAKARTA - Zeta Chandra, Dheandra; Purwana, Dedi; Adha, Maulana (Transpublika Publisher, 2023)
Cashless transactions offer the advantages of simpler, faster, and safer transactions compared to non-cash transactions, and can increase economic activity in a country. To support digital payments, BI released QRIS as a national QR code standard. The utilization of QRIS as a payment channel has increased every year. This research focuses on the strategy of Bank Indonesia Jakarta Representative Office in developing non-cash payments through QRIS for MSMEs in Jakarta, the impact of non-cash payment development strategies through QRIS, and constraints on non-cash payment development strategies. This research is a field study using a descriptive qualitative research approach. The results of this study show that there are several strategies including conducting socialization, including MSMEs in BI strategic events, connecting with Perumda Pasar Jaya traditional markets which were later designated as S.I.A.P QRIS markets, and receiving complaints about QRIS. As an impact of the strategy of developing cashless payments through QRIS, the findings of this study show how QRIS shortens the payment process and makes transactions more secure for both merchants and consumers. On the other hand, people's dependence on cash transactions and public understanding of payments through QRIS are the main challenges faced by Bank Indonesia Jakarta Representative Office in implementing non-cash payments through QRIS for MSMEs in Jakarta.